Analysis of the economic-financial viability of basic sanitation service models in the municipalities of Amazonas: a case study of the municipality of Itacoatiara - Santos, Naedno Augusto Dolzane dos; Marques, Evely Laranjeira; Alves, Rodrigo Couto (Brazilian Journal of Production Engineering, 2024)
Basic sanitation is seen as a fundamental right in Brazil, which is governed by Law 11,445/2007, which aims to universalize water supply, sewage and solid waste management services. In view of this, in the state of Amazonas, especially in its 62 municipalities, we can mention the several significant challenges facing this universalization. Furthermore, a reduction in fees is made possible, in accordance with the New Legal Framework for Basic Sanitation, but with the exception of Manaus. Therefore, this study aims to analyze the economic and financial accessibility of basic sanitation management models in the municipalities of Amazonas, essentially in the Autonomous Water and Sewage Service (SAAE) of Itacoatiara. However, despite the data from the National Sanitation Information System (SNIS) being reviewed, the lack of consistent information in the models was noted, which consequently made it difficult to use them in this analysis. Therefore, the assessment of SAAE was based only on the financial statements from 2020 to 2022. Thus, the results indicated that the SAAE of the municipality of Itacoatiara remained financially stable, through initiatives originating from implementations aimed at optimizing costs and strict control of revenues. Thus, despite good management, there are still difficulties to be faced, such as fluctuations in revenue and problems with default. That said, there is a need for greater transparency and strategic planning in order to certify long-term financial sustainability. Finally, we can conclude that supervision and improved transparency are essential to improve the viability and effectiveness of sanitation services provided in this state.